Tradeborder: Internet of Things Based Application to Improve the Welfare of MSME Actors on the West Kalimantan Border Through Indonesia-Malaysia Trade Relations - Hasibuan, Rizki Alfitra; Yunita, Arma Sri (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2024)
The state border area in West Kalimantan includes 5 districts, namely Sambas, Bengkayang, Sanggau, Sintang and Kapuas Hulu districts. From a socio-economic perspective, border areas in West Kalimantan Province generally have the main problem, namely their isolated/underdeveloped location with a low level of accessibility and a low level of social welfare for border communities. One of the efforts to improve the welfare of people in border areas is to increase people's income through empowering the rural economy, especially increasing MSMEs. Furthermore, the increasingly rapid technological transformation is making innovations from traditional strategies change to digital strategies. Therefore, the author proposes an Internet of Things-based application to improve the welfare of MSMEs on the West Kalimantan border in the bilateral trade relations between Indonesia and Malaysia, namely the TradeBorder application.